The Influence of Digital Competence and Personality Competence on the Creativity of Madrasah Ibtidaiyah Teachers in Dukun Subdistrict - Shofiah, Ni’matus; Riyanto, Yatim; Khamidi, Amrozi (Journal of Educational Sciences, 2025)
Education 4.0 requires teachers to possess high creativity supported by digital competence and a mature personality. This study aims to analyze the influence of digital competence and personality competence on the creativity of Madrasah Ibtidaiyah teachers in Dukun District. This study employs a quantitative approach with a descriptive correlational design. The population comprised 554 teachers, with a sample of 232 teachers selected using Cluster Area Probability Random Sampling technique. Data collection instruments included a test for digital competence and questionnaires for personality and creativity variables, which were analyzed using multiple linear regression. The results indicated that the levels of digital competence, personality competence, and teacher creativity were in the moderate category. Statistically, there is a significant influence, both partially and simultaneously, of digital competence and personality competence on teacher creativity. The conclusion emphasizes that the integration of technological mastery and personality maturity is a fundamental factor that must be enhanced continuously to foster teacher creativity in creating innovative learning.